Palbociclib impairs the proliferative capacity of activated T cells while retaining their cytotoxic efficacy - Arndt, Claudia; Tunger, Antje; Wehner, Rebekka; Rothe, Rebecca; Kourtellari, Eleni; Luttosch, Stephanie; Hannemann, Katharina; Koristka, Stefanie; Loureiro, Liliana R.; Feldmann, Anja; Tonn, Torsten; Link, Theresa; et al. (Frontiers in Pharmacology, 2023)
The cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitor palbociclib is an emerging cancer therapeutic that just recently gained Food and Drug Administration approval for treatment of estrogen receptor (ER)-positive, human epidermal growth factor receptor (Her)2-negative breast cancer in combination with the ER degrader fulvestrant. However, CDK4/6 inhibitors are not cancer-specific and may affect also other proliferating cells. Given the importance of T cells in antitumor defense, we studied the influence of palbociclib/fulvestrant on human CD3+ T cells and novel emerging T cell-based cancer immunotherapies. Palbociclib considerably inhibited the proliferation of activated T cells by mediating G0/G1 cell cycle arrest. However, after stopping the drug supply this suppression was fully reversible. In light of combination approaches, we further investigated the effect of palbociclib/fulvestrant on T cell-based immunotherapies by using a CD3-PSCA bispecific antibody or universal chimeric antigen receptor (UniCAR) T cells. Thereby, we observed that palbociclib clearly impaired T cell expansion. This effect resulted in a lower total concentration of interferon-g and tumor necrosis factor, while palbociclib did not inhibit the average cytokine release per cell. In addition, the cytotoxic potential of the redirected T cells was unaffected by palbociclib and fulvestrant. Overall, these novel findings may have implications for the design of treatment modalities combining CDK4/6 inhibition and T cell-based cancer immunotherapeutic strategies.